Removal Technique of Penetrating Nail in Head: A Case Report - Suhendar, Agus; Effendy, Effendy (Faculty of Medicine Universitas Padjadjaran, 2023)
Objective: To present a unique case involving a 44-year-old man who sustained a penetrating head injury after nailing his head with a hammer. Despite the severity of his injury, the patient underwent successful surgical treatment and experienced a good recovery.Methods: Clinical and imagery review was performed on a cranial puncture trauma caused by a metal nail, which penetrated the cranium, dura mater, right parietal cerebral parenchyma, and right ventricle. The nail was lodging next to midline without damaging the superior sagittal sinus. The patient underwent craniotomy nail removal and debridement with normal saline and metronidazole antibiotics.Results: Craniotomy, careful nail extraction, wound debridement, and duraplasty remain the treatment standard for penetrating nail injury in the head. Patient in this case study did not exhibit any signs of neurologic deficit or infection.Conclusion: Proper diagnosis and treatment are required in patients with penetrating brain trauma, with head x-rays and CT scans help in evaluating vascular depth and damage. Craniotomy and debridement are the main treatments for this type of trauma.